La obra de Luis Humberto Crosthwaite: frontera sin límites - Romero, Miriam S (My University, 2016)
This analysis focuses on the literary works of the Mexican writer Luis Humberto Crosthwaite. The principal objective of this study is to show how Crosthwaite’s works are innovative forms of borderlands literature. Although some literary scholars have criticized Crosthwaite as monothematic and boring, through the succinct analysis of his creative writing and the use of different literary concepts such as rhizome, chronotope, liminality, and third space, this dissertation demonstrates that his works encompass not only themes from Mexico-United States border culture and language, but they also expand beyond border topics. Consequently, Crosthwaite creates a form of literature that is diverse and heterotopic.
Keywords: Latin American Literature; Mexican Literature; Borderlands Literature